Model Supervision Deep Development Of Learning Quality Islamic Boarding School in Jambi City - Siti Ubaidah; Siti Asiah (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
This research aims to describe the application of the academic supervision model to supervisors in developing Islamic religious education teachers in Pondok Jambi City Faith Islamic Boarding School and Jambi City As'ad Islamic Boarding School. This research is a qualitative research with a phenomenological approach. The subject of this research is the supervisor, chairman Madrasah, teachers and students at the Nurul Iman Islamic Boarding School, Jambi City and As'ad, Jambi City. Data collection The techniques used are observation, interviews and documentation. Processing technique and data analysis through data reduction, data presentation, and verification or withdrawal.Conclusion The research results show that the implementation of academic supervision supervisor of the Nurul Iman Islamic Boarding School in Jambi City and the As'ad Islamic Boarding School in Jambi City From a planning aspect, a monitoring program has been included because The supervisor has carried out planning before carrying out supervision activities by making agreement with the madrasah personnel who will be supervised so that they prepare themselves. However, that is The teacher development aspect has not gone well, so have many aspects of assessment. These are the results of the implementation of the supervisor's academic supervision on development of Islamic religious education teachers in Pondok The Nurul Iman Islamic Boarding School in Jambi City and the As'ad Islamic Boarding School in Jambi City are not yet optimal so they still need to be done improved, especially in the development and assessment aspects